The smart city, a strategy for sustainable urban development - Saouli, Rim Amina; Benhassine, Nassira (Journal of Architecture and environment of child, 2021)
Using holistic, exploratory-descriptive, and case study research methodologies to achieve the objective of this article, which is to understand how to achieve sustainability in cities via the development of smart cities, our investigation begins with a review of the relevant literature to uncover the many sources that study the term "smart city" and its context. The paper then provides an overview of sustainable smart cities around the world that use information and communication technologies (ICT) to improve their quality of life. As we attempt to describe in this paper, the topic of study covered by this paper is how to achieve sustainability through the implementation of smart cities. The investigation focuses on the concept of "smart city" as a strategy for sustainable urban development, using case studies of Singapore and Amsterdam as examples.